2012
DOI: 10.1136/postgradmedj-2011-130121
|View full text |Cite
|
Sign up to set email alerts
|

Hospital consultants and workplace based assessments: how foundation doctors view these educational interactions?

Abstract: Completion of foundation doctors' assessments by hospital consultants is viewed as a low priority. These assessments are being completed to a large extent by fellow doctors in training. The learning opportunities are consequently less educationally productive. F2 doctors want more opportunities for valued consultant interaction with timely feedback. Suggestions are proposed to improve WPBA implementation. The present WPBA process lacks integrity and a change in approach is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 24 publications
0
58
1
Order By: Relevance
“…Firstly, all three perspectives require assessors to actually observe trainees interacting with patients and all recognise that the current quantity and frequency of observation‐based assessment of undergraduate and postgraduate medical trainees is less than ideal. This is a serious deficiency in assessment programmes, which requires immediate attention . Regardless of the perspective on assessor cognition, institutions must create clinical and medical education systems that permit, promote and sustain direct observation of trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, all three perspectives require assessors to actually observe trainees interacting with patients and all recognise that the current quantity and frequency of observation‐based assessment of undergraduate and postgraduate medical trainees is less than ideal. This is a serious deficiency in assessment programmes, which requires immediate attention . Regardless of the perspective on assessor cognition, institutions must create clinical and medical education systems that permit, promote and sustain direct observation of trainees.…”
Section: Discussionmentioning
confidence: 99%
“…A large majority felt that incompetent trainees could achieve satisfactory results from the WBPAs, while a large percentage of FY doctors felt that the regulatory process did not give them an adequate opportunity to highlight any training problems. This adds weight to the argument that the current WBPA process appears to lack integrity 22 and that WBPAs should not be relied upon to certify competence. 21 …”
Section: Discussionmentioning
confidence: 99%
“…These concerns reflect criticisms of workplace‐based assessment in Australia and abroad . Both junior doctors and assessing consultants have reported a lack of time and interest in the process, resulting in grades that are arbitrary, unreliable and lacking in specific feedback . Quantitative studies have demonstrated significant skewing towards positive results and a failure to identify junior doctors at risk of difficulty …”
Section: Discussionmentioning
confidence: 99%